Urgensi Nilai Akidah dan Tauhid dalam Membentuk Karakter Islami Berbasis Budaya: Penelitian - Marlizayani; Jarir; Faridah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Aqidah tauhid serves as the fundamental foundation in shaping a strong Islamic character rooted in faith-based values. Within the context of Malay society, tauhid is not a standalone concept but is closely intertwined with local cultural values such as politeness, respect for elders, and social responsibility. Rich in local wisdom, Malay culture holds great potential as a medium for internalizing tauhid values among the younger generation. Islamic education that combines aqidah teachings with cultural approaches is considered more effective, as it engages both the emotional and social aspects of students. This study employs a qualitative descriptive approach through literature review of relevant scientific articles. The findings reveal that the synergy between aqidah tauhid and Malay culture strengthens the development of religious, honest, and noble character in students. The local cultural context helps learners to understand Islamic values in a more grounded and relatable manner. Culturally-based education not only preserves cultural identity but also serves as an effective means of instilling sustainable spiritual values.